Biodeterioration of Compost-Pretreated Polyvinyl Chloride Films by Microorganisms Isolated From Weathered Plastics - Novotný, Čenek; Fojtík, Jindřich; Mucha, Martin; Malachová, Kateřina (Frontiers in Bioengineering and Biotechnology, 2022)
Polyvinyl chloride (PVC) is a petroleum-based plastic used in various applications, polluting the environment because of its recalcitrance, large content of additives, and the presence of halogen. In our case study, a new, two-stage biodegradation technology that combined composting process used for PVC pretreatment with a subsequent PVC attack by newly-isolated fungal and bacterial strains under SSF conditions was used for biodegradation of commercial PVC films. The novelty consisted in a combined effect of the two biodegradation processes and the use for augmentation of microbial strains isolated from plastic-polluted environments. First, the ability of the newly-isolated strains to deteriorate PVC was tested in individual, liquid-medium- and SSF cultures. Higher mass-reductions of PVC films were obtained in the former cultures, probably due to a better mass transfer in liquid phase. Using the two-stage biodegradation technology the highest cumulative mass-reductions of 29.3 and 33.2% of PVC films were obtained after 110 days with Trichoderma hamatum and Bacillus amyloliquefaciens applied in the 2nd stage in the SSF culture, respectively. However, FTIR analysis showed that the mass-reductions obtained represented removal of significant amounts of additives but the PVC polymer chain was not degraded.